Low-Power Active RFID System Using nRF24L01 - Ahmad Azzreen, Dalawi; Fahmi, Samsuri (Universiti Malaysia Pahang, 2016)
A low-power active Radio Frequency Identification (RFID) system based on nRF24L01 RF transceiver is designed and implemented. The nRF24L01 is used to act as both reader and active tag of RFID system respectively. The nRF24L01 is chosen due to its low-power and it also operates at 2.4 GHz in which lies on ultra-high frequency (UHF) band. Significant power consumption is reduced by operating in standby mode, transmitting mode and receiving mode at 29µA, 10.25mA and 6.92mA current rating respectively. In addition, nRF24L01 can interact with microcontroller which retain the circuit simplicity.